How do impact investors leverage non-financial strategies to create value An impact-oriented value framework - Justo, Rachida; Nachyla, Pola (Science Direct, 2023)
One of the ways to understand the success of impact investing firms is to examine how they add value to the social enterprises they invest. Did their investment boost social and/or environmental change? And what type of support, beyond financial capital, can they provide to enhance impact? Drawing on a design-based methodology, we seek to address some of these questions by developing a tool called the Impact Oriented Value Framework. Putting impact at the centre of the funds' purpose, the framework provides actionable solutions to infuse impact into investors’ non-financial support strategies and activities, enhancing their additionality to portfolio companies as well as their contribution to the impact ecosystem.
Keywords: 53 Ciencias Económicas; ODS 8 - Trabajo decente y crecimiento económico